2009
DOI: 10.1002/humu.21116
|View full text |Cite
|
Sign up to set email alerts
|

CC2D2Amutations in Meckel and Joubert syndromes indicate a genotype-phenotype correlation

Abstract: The Meckel syndrome (MKS) is a lethal fetal disorder characterized by diffuse renal cystic dysplasia, polydactyly, a brain malformation that is usually occipital encephalocele and/or vermian agenesis, with intrahepatic biliary duct proliferation. Joubert syndrome (JBS) is a viable neurological disorder with a characteristic "molar tooth sign" (MTS) on axial images reflecting cerebellar vermian hypoplasia/dysplasia. Both conditions are classified as ciliopathies with an autosomal recessive mode of inheritance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 29 publications
(50 reference statements)
6
77
0
2
Order By: Relevance
“…19 This would be in line with the observation that mild mutations in MKS-associated genes can cause JBS, for example, RPGRIP1L/MKS5 and CC2D2A/MKS6. 35,36 The patient presented with a mild classic JBS phenotype without renal, retinal, or hepatic disease (at age 10 years), similar to the phenotype of two JBS cases with B9D1 mutations described recently. 19 The percentage of JBS cases with a heterozygous mutation in a known JBS gene (53%) is much higher than expected in a rare autosomal recessive disease (the estimated birth prevalence of JBS is 1 in 80 000 to 1 in 100 000); 2,7 however, we cannot exclude that a second pathogenic mutation is present but missed by our detection method.…”
Section: Non-mendelian Inheritance and B9d1supporting
confidence: 70%
“…19 This would be in line with the observation that mild mutations in MKS-associated genes can cause JBS, for example, RPGRIP1L/MKS5 and CC2D2A/MKS6. 35,36 The patient presented with a mild classic JBS phenotype without renal, retinal, or hepatic disease (at age 10 years), similar to the phenotype of two JBS cases with B9D1 mutations described recently. 19 The percentage of JBS cases with a heterozygous mutation in a known JBS gene (53%) is much higher than expected in a rare autosomal recessive disease (the estimated birth prevalence of JBS is 1 in 80 000 to 1 in 100 000); 2,7 however, we cannot exclude that a second pathogenic mutation is present but missed by our detection method.…”
Section: Non-mendelian Inheritance and B9d1supporting
confidence: 70%
“…Despite two patients displaying an occipital encephalocele, no ARL13B variants have been found in Meckel syndrome fetuses (Cantagrel et al 9 and personal data), although Meckel syndrome has been shown to be the extreme lethal phenotype of JS for other genes. [29][30][31][32][33] In conclusion, we have identified a novel homozygous missense variant in ARL13B/JBTS8 in a JS patient with retinal involvement and obesity. We have shown that this variant is hypomorphic, as it is unable to rescue efficiently either the arl13b sco zebrafish phenotype or the deficiencies in Arl13b hnn MEFs.…”
Section: Discussionmentioning
confidence: 67%
“…This protein was therefore named CC2D, standing for coiled-coil-and C2-domain-containing protein. Proteins with similar domain organization have also been found in other organisms, and the human CC2D2A protein has been located to the cilia basal bodies and been implicated in ciliogenesis and human ciliary diseases (Doherty, 2009;Gorden et al, 2008;Mougou-Zerelli et al, 2009;Noor et al, 2008;Tallila et al, 2008).…”
Section: T Brucei Cc2dmentioning
confidence: 98%